Role of Radiation Based Conditioning Regimens in Patients With High-Risk AML Undergoing Allogenic Transplantation in Remission or Active Disease and Mechanisms of Post-Transplant Relapse - Amandeep Salhotra; Anthony Selwyn Stein (Frontiers in Oncology, 2022)
In the two decades there has been a consistent improvement in the clinical outcomes of patients diagnosed with acute leukemia undergoing allogenic stem cell transplantation. These improvements have been made possible by advancements in supportive care practices, more precise risk stratification of leukemia patients by genetic testing at diagnosis, accurate disease assessment by measurable residual disease (MRD) in pretransplant marrow and attempts to clear residual disease clones prior to transplant. Availability of targeted therapies, immunotherapies, and approval of novel drug combinations with BCL-2 inhibitors has also improved remission rates for patients who are undergoing transplant. For patients who are unable to achieve a morphologic or MRD- remission prior to transplant, the risk of relapse post-transplant remains high. Total body irradiation (TBI) based intensification of transplant conditioning may be able to overcome risk of increased relapse rate in this clinical setting by improving clearance of leukemic clones. However, in the past increased nonrelapse mortality (NRM) associated with escalation of conditioning intensity has neutralized any potential benefit of decreasing relapse rate in HCT patient resulting in no significant improvement in overall survival. In this review we discuss incorporation of newer radiation techniques such as total marrow irradiation (TMI) to safely deliver targeted doses of radiation at higher doses to improve outcomes of patients with active leukemia. We also discuss the mechanisms associated with leukemia relapse and treatment options available in post allo-HCT relapse setting despite use of intensified conditioning regimens.